Psychosocial interventions for adults with newly diagnosed chronic disease: A systematic review. (June 2022) - Akyirem, Samuel; Forbes, Angus; Wad, Julie Lindberg; Due-Christensen, Mette
While the need for psychosocial interventions in the early formative period of chronic disease diagnosis is widely acknowledged, little is known about the currently available interventions and what they entail. This review sought to collate existing interventions to synthesize their active ingredients. A systematic search on five electronic databases yielded 2910 records, 12 of which were eligible for this review. Evidence synthesis revealed three broad categories of interventions which used at least two out of eight active techniques. Future studies should adhere to known frameworks for intervention development, and focus on developing core outcome measures to enhance evidence synthesis